Strategi Desain Pembelajaran Adaptif Untuk Meningkatkan Pengalaman Belajar di Era Digital - Yuda Al Fadillah; Alifa Rafli Akbar; Gusmaneli (CV.ITTC INDONESIA, 2024)
Adaptive learning supported by digital technologies, such as artificial intelligence (AI), big data, and online learning platforms, has great potential to improve student engagement and learning outcomes. By adapting course material to each student's abilities, learning style and pace, this course allows for a more personalized and effective learning experience. However, in Indonesia, the main challenges faced in its implementation are the digital divide between urban and rural areas and the readiness of teachers to use technology. Improving technological infrastructure and training for educators is very necessary to maximize the potential of adaptive learning. This research aims to identify challenges and opportunities in implementing adaptive learning in Indonesia, as well as how technology can be optimized to support the development of more inclusive and effective education.